High gas sensing performance of inorganic and organic molecule sensing devices based on the BC3N2 monolayer. Issue 38 (26th September 2022) - Liu, Guogang; Chen, Tong; Dong, Xiansheng; Huang, Lin; Xu, Zhonghui; Xiao, Xianbo
Abstract : The adsorption analysis revealed that the BC3 N2 -based gas sensors have a strong anisotropy, showing high gas sensitivity to the organic gas molecule C2 H2 . Abstract : Recently, a novel two-dimensional (2D) BC3 N2 monolayer has gained a lot of attention due to its graphene-like structure, and it was first reported by using the particle swarm optimization algorithm and ab initio calculations. Combining density functional theory with the non-equilibrium Green's function method, a 2D BC3 N2 -based nanodevice has been theoretically constructed and the gas sensing performance of the BC3 N2 monolayer for inorganic and organic molecules has been extensively investigated. The results revealed that the BC3 N2 monolayer remains metallic with thermodynamic stability. Meanwhile, the results of sensing performance analysis show that the inorganic molecules CO, NO, and NO2 and organic molecules C2 H2 and HCHO have strong chemical interactions with BC3 N2 and were chemically adsorbed onto BC3 N2 . In contrast, the interactions between NH3, SO2, CH4, C2 H4 and CH3 OH and BC3 N2 are very weak and these molecules adopt physical adsorption. In the case of chemisorption, the electronic transport behaviors of the 2D BC3 N2 devices are sensitive to molecules, and the gas sensitivity of BC3 N2 is strongly anisotropic, especially for organic C2 H2 with the gas sensing ratios from 7.30 to 10.43 (from 2.51 to 2.79) under different bias voltages along the zigzag (armchair) direction. For inorganic molecules, the gas sensing device is not particularly sensitive, and the maximum gas sensing ratio is only 1.36 for CO. Meanwhile, the large anisotropic gas sensitivity can reach up to 2.66/6.22 for electron transport along the armchair and zigzag directions for CO/C2 H2 in the BC3 N2 -based sensing devices. Accordingly, the high gas sensitivity can be disclosed by displaying the scattering state around the Fermi level at different bias voltages during the transport process. As a result, BC3 N2 could be used in 2D gas sensing devices, especially for sensing organic molecule C2 H2 .